A case report of Asymptomatic hyperCKemia and literature review - Luo, Meng; Huang, Xuerong; Wang, Wenhui; He, Qingjun; Zhou, Chunhong; Lin, Yingyu; Fan, Chunxiao; Pi, Jianbin (Journal of the Pakistan Medical Association, 2025)
The case report of a female with Asymptomatic hyperCKemia along with a literature review is presented. The objective of this report is to highlight an effective diagnosis and treatment option for Asymptomatic hyperCKemia patients, as well as to bring to attention a rare and benign cause of CK elevation, which can lead to diagnostic and therapeutic errors. Key words: Asymptomatic hyperCKemia; Rare disease.